THE EFFECT OF WORKLOAD AND EMPLOYEE ENGAGEMENT ON EMPLOYEE JOB SATISFACTION AT BUN KOPI IN BANDAR LAMPUNG - Hendri Dunan; Fatiya Husna Syarofa (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - This study aims to analyze the effect of workload and employee involvement on job satisfaction at BUN Kopi Bandar Lampung, focusing on how internal work conditions influence employee attitudes and well-being.METHODOLOGY - Population study This consists of from all over BUN Kopi Bandar Lampung workers (24 hours) spread across three outlets: BUN Kopi Kedaton, BUN Kopi Rawa Laut, and BUN Kopi UNILA, with a total of 64 employees. Approach taking samples used is saturation sample (census), which means all over population used as respondents. Package for the Social Sciences (SPSS) software version 30. Descriptive tests, multiple linear regression, and statistical tests hypothesis partial and simultaneous included among approach analysis of the data used.FINDING - Findings show that burden work no own impact substantial to satisfaction work employees. Meanwhile that, involvement employee proven own beneficial and sufficient impact big to satisfaction Work employees. At BUN Kopi in Bandar Lampung, satisfaction work employee influenced in a way positive and significant by load work and involvement employees. Findings this show that involvement employee with work and business important in increase satisfaction work, so that management need emphasize management source power man.